Effectiveness and Clinical Indications of 2 × 4 Fixed Orthodontic Therapy in Regard to Mixed Dentition: A Systematic Review - Gianna Dipalma; Grazia Marinelli; Lucia Casamassima; Paola Nardelli; Danilo Ciccarese; Paolo De Sena; Francesco Inchingolo; Vito Crincoli; Andrea Palermo; Ioana Roxana Bordea; Andrea Carbonara; Angelo Michele Inchingolo; et al. (Children)
Background/Objectives: This systematic review examines the effectiveness and clinical indications of the 2 × 4 fixed orthodontic appliance for interceptive treatment in children with mixed dentition, aiming to simplify future orthodontic needs. Methods: Following the PRISMA guidelines, a search was conducted across PubMed, Web of Science, and Scopus (May 2000–May 2025). The inclusion criteria focused on open-access, in vivo/human studies, case–control studies, cohort studies, and RCTs in English. Risk of bias was assessed using Rob 2.0. Results: Out of 362 initial records, 7 studies were included. Most of the included studies showed a low risk of bias, with some moderate risk in terms of confounding variables and participant selection, but no high risk was identified. Conclusions: The 2 × 4 fixed orthodontic appliance is an effective interceptive therapy for mixed dentition. Clinicians can optimize outcomes by understanding its biomechanics and clinical applications. Further research is needed to understand long-term impacts and improve efficiency.